Self-healing nanocomposites via N-doped GO promoted "click chemistry". Issue 1 (6th December 2022) - Sanka, R. V. Siva Prasanna; Rana, Sravendra; Singh, Poonam; Mishra, Abhishek K.; Kumar, Pankaj; Singh, Manjeet; Sahoo, Nanda Gopal; Binder, Wolfgang H.; Yun, Gun Jin; Park, Chanwook
Abstract : N-Doped graphene stabilized Cu(i )-catalyzed self-healing nanocomposites are developed, where N-doped graphene is helpful to enhance mechanical and conductive properties as well as catalyst promoter helpful to trigger self-healing via click chemistry. Abstract : N-doped graphene stabilized Cu(i )-catalyzed self-healing nanocomposites are developed. This study found the use of N-doped graphene as both a nanostructured material for enhancing mechanical and conductive properties and a catalyst promoter (a scaffold for catalytic copper(i ) particles), helpful to trigger self-healing via "click chemistry". Due to an increase in electron density on nitrogen atom doping, including the coordination of N-doped rGO with Cu + ions, nitrogen-doped graphene-supported copper particles demonstrate a higher reaction yield at room temperature without adding any external ligand/base. In this study, only one component (an azide moiety containing a healing agent) was encapsulated, whereas another component (an alkyne moiety containing a healing agent) was as such (without encapsulation) homogeneously dispersed in a matrix. Triggered capsule rupture then induces the contact of the healing agents with the N-doped graphene-based catalyst and the alkyne molecules dispersed in the matrix, inducing a "click"-reaction, allowing onsite damage to be repaired as determined by mechanical measurements entirely. Tensile measurements were also performed using molecular dynamics (MD) simulations to support the findings. Given the enormous importance of autonomic repair of materials damage, this concept here reports a trustworthy and reliable chemical system with a high level of robustness.